Preparation and characterization of graphite composites of polyaniline - Ozerol, E. Ahlatcioglu; Senkal, B. F.; Okutan, M. (ELSEVIER, 2015)
In this work, synthesis and characterization of composite materials based on graphite (GH) and boric acid doped polyaniline (PANI) was studied. PANI + GH composites were prepared via a simple in situ polymerization of aniline in graphite dispersion. The resulting composites of the PANI + GH were characterized by using spectroscopic, morphologic and physical methods. Ac conductivity and electronic properties of PANI doped 2%, 5% and 10% GHs have been investigated by impedance spectroscopy within the frequency interval of 10 kHz-15 MHz. The frequency dependence of ac conductivity (sigma(AC)) of PANI and PANI + GH composites have been investigated by means of frequency exponent s parameter in the low and high frequency regions. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Graphite; PANI; Conducting polymer; Composites; Engineering; Science & Technology - Other Topics; Optics; Physics